A Signature Based on Costimulatory Molecules for the Assessment of Prognosis and Immune Characteristics in Patients With Stomach Adenocarcinoma - Chen, Bangjie; Yao, Yong; Mao, Deshen; Li, Conghan; Wang, Xingyu; Sheng, Shuyan; Zhang, Lizhi; Wang, Xinyi; Chen, Sanwei; Xu, Wentao; Deng, Jianyi; Sun, Chenyu; et al. (Frontiers in Immunology, 2022)
Although costimulatory molecules have been shown to boost antitumor immune responses, their significance in stomach adenocarcinoma (STAD) is unknown. The purpose of this study was to examine the gene expression patterns of costimulatory molecule genes in STAD and to develop a predictive signature to aid in therapy selection and outcome prediction. We used 60 costimulatory family genes from prior research to conduct the first complete costimulatory molecule analysis in STAD patients. For the two groups discovered, consensus clustering analysis based on these 60 genes indicated unique distribution patterns and prognostic differences. Then, using Lasso and Cox regression analysis, 9 costimulatory molecular gene pairs (CMGPs) of prognostic value were discovered. With these 9 CMGPs, we were able to develop a costimulatory molecule-related prognostic signature, which performed well in an external dataset. For STAD patients, the signature was proved to be a risk factor independent of clinical characteristics, indicating that this may be employed in conjunction with clinical considerations. An further connection between the signature and immunotherapy response was discovered. People who had high mutation rates, an abundance of infiltrating immune cells, and an immunosuppressive milieu were classed as high-risk. It is possible that patients classed as high-risk have a better prognosis for immunotherapy since these patients have greater cytolytic activity scores and immunophenoscores of CTLA4 and PD-L1/PD-L2 blocker As a consequence, clinicians might use our signature to better assess patient prognosis and develop treatment plans.